Metabolomics Analysis of the Effect of Glutamic Acid on Monacolin K Synthesis in Monascus purpureus - Zhang, Chan; Zhang, Nan; Chen, Mengxue; Wang, Haijiao; Shi, Jiachen; Wang, Bei; Sun, Baoguo; Wang, Chengtao (Frontiers in Microbiology, 2020)
Monacolin K is a secondary metabolite produced by Monascus with beneficial effects on health, including the ability to lower cholesterol. We previously showed that the yield of monacolin K was significantly improved when glutamic acid was added to the fermentation broth of Monascus purpureus M1. In this study, we analyzed M. purpureus in medium with and without glutamic acid supplementation using a metabolomic profiling approach to identify key metabolites and metabolic pathway differences. A total of 817 differentially expressed metabolites were identified between the two fermentation broths on day 8 of fermentation. Pathway analysis of these metabolites using the KEGG database indicated overrepresentation of the TCA cycle, biotin metabolism, and alanine, aspartate, and glutamate metabolic pathways. Six differentially expressed metabolites were found to be related to the citric acid cycle. The effect of citric acid as an exogenous additive on the synthesis of monacolin K was examined. These results provide technical support and a theoretical basis for further studies of the metabolic regulatory mechanisms underlying the beneficial effects of monacolin K and medium optimization for, and genetic engineering of Monascus M1 for efficient monacolin K production.